ANALISIS STABILITAS DAN JUSTIFIKASI TEKNIS PERKUATAN STRUKTUR PADA TANAH LUNAK (STUDI KASUS : REHABILITASI DAERAH IRIGASI GLAPAN TIMUR DAN BARAT) - suudi al mukarom; Ian Karunia Perkasa; Salsabila Zahra (Universitas Mulawarman, 2026)
This study presents a technical justification for structural reinforcement in the rehabilitation of the Glapan Irrigation Area Phase II, focusing on soft soil conditions prone to sliding failure. The research aims to evaluate the stability of the existing lining structure and to determine an appropriate reinforcement method. The methodology includes field investigation, geotechnical analysis, slope stability evaluation, and assessment of alternative reinforcement solutions. The results indicate that the existing structure does not meet the minimum safety requirements, with a safety factor of 1.15 against sliding, which is below the standard value of 1.5. To address this issue, a minipile system is proposed as the most effective reinforcement solution. The designed minipile, with a diameter of 20 cm and a depth of 3–4 meters, significantly improves structural performance. The analysis shows that the safety factor increases to 2.15 after reinforcement, indicating a substantial enhancement in stability. This study provides a technically justified recommendation for design modification, ensuring structural safety and long-term performance under soft soil conditions. The findings contribute to improving the reliability of irrigation infrastructure in similar geotechnical environments.